The Holy Spirit in the world: a global conversation - Kim, Kirsteen (SPCK, Society for Promoting Christian Knowledge, 2008)
The spirit in the world : church, believer, "everywhere" -- The spirit in the Bible : Pentecost, Christ, creation -- The spirit of mission impulse, guidance, and power -- The mission of the spirit unity, creation, history -- Mission in the spirit dialogue, inculturation, liberation -- Mission among the spirits release, blessing, harmony -- Theology of the Holy Spirit in a plural world : spirits, spiritualities, discernment